Integrated assessment of the serum magnesium-to-vitamin D3 ratio, micronutrient deficiencies, and inflammatory biomarkers in patients with migraine - Alrahman, R. A.; Jabbar, L.; Shalal, S. H. (Regulatory Mechanisms in Biosystems, 2026)
Migraine is a common neurovascular disease linked to complex metabolic or inflammatory changes that can lead to neuronal hyperexcitability and susceptibility to headache. In this study, associations between the serum magnesium-to-vitamin D 3 (Mg/VitD 3 ) ratio and other micronutrients and inflammatory biomarkers were evaluated and examined as a combined biochemical index in patients with migraine. A case - control study was carried out with 120 adult participants (60 migraine patients and 60 healthy controls of matched age and sex ) . The level of serum magnesium was determined by an automated colorimetric method, and 25-hydroxyvitamin D 3 was determined by enzyme-linked immunosorbent assay (ELISA). Serum calcium, vitamin B 12 , folic acid and C-reactive protein (CRP) were also measured. A Mg/VitD 3 ratio was determined for each individual. There were no significant differences between the two groups for any baseline demographic characteristics. Migraine patients exhibited significantly lower serum vitamin D 3 (18.1 ± 3.2 vs. 28.6 ± 4.3 ng/mL), magnesium (1.39 ± 0.22 vs. 2.00 ± 0.19 mg/dL), calcium (9.08 ± 0.51 vs. 9.32 ± 0.28 mg/dL), vitamin B12 (421.8 ± 193.6 vs. 489.4 ± 87.5 pg/mL), and folic acid (5.7 ± 1.3 vs. 12.4 ± 3.2 ng/mL), whereas CRP levels were markedly elevated (2.56 ± 1.31 vs. 0.48 ± 0.18 mg/L). The Mg/VitD 3 ratio was significantly reduced in migraine patients. All significant correlations were positive, with a strong positive correlation with magnesium (r = 0.843) and vitamin D 3 (r = 0.721); moderate positive correlations with folic acid, vitamin B 12 , and calcium; and a strong negative correlation with CRP (r = −0.589). Only magnesium, vitamin D 3 , folic acid, vitamin B 12 and CRP were independently associated with migraine (logistic regression analysis), while calcium was not. There is also concurrent micronutrient deficiency and syste m ic inflammation in migraine. The ratio of Mg/VitD 3 in serum is a promising integrated biomarker that includes metabolic and inflammatory disturbances and could have the potential to enhance biochemical evaluation and risk stratification in patients with migraine.